Fabrication of three-dimensional proteinaceous micro- and nano-structures by femtosecond laser cross-linking - Serien Daniela (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
Proteins are a class of biomaterials having a vast array of functions, including the catalysis of metabolic reactions, DNA replication, stimuli response and transportation of molecules. Recent progress in laser-based fabrication technologies has enabled the formation of three-dimensional (3D) proteinaceous micro- and nano-structures by femtosecond laser cross-linking, which has expanded the possible applications of proteins. This article reviews the current knowledge and recent advancements in the femtosecond laser cross-linking of proteins. An overview of previous studies related to fabrication using a variety of proteins and detailed discussions of the associated mechanisms are provided. In addition, advances and applications utilizing specific protein functions are introduced. This review thus provides a valuable summary of the 3D micro- and nano-fabrication of proteins for biological and medical applications.